Differential Effects of 2-Deoxyglucose and Glucose Deprivation on 4-Hydroxynonenal Dependent Mitochondrial Dysfunction in Primary Neurons - Dodson, Matthew; Benavides, Gloria A.; Darley-Usmar, Victor; Zhang, Jianhua (Frontiers in Aging, 2022)
Mitochondrial dysfunction and metabolic decline are prevalent features of aging and age-related disorders, including neurodegeneration. Neurodegenerative diseases are associated with a progressive loss of metabolic homeostasis. This pathogenic decline in metabolism is the result of several factors, including decreased mitochondrial function, increased oxidative stress, inhibited autophagic flux, and excessive or insufficient availability of certain metabolic substrates. One critical metabolite for maintaining neuronal function is glucose, which is utilized by the brain more than any other organ to meet its substantial metabolic demand. Enzymatic conversion of glucose into its downstream metabolites is critical for maintaining neuronal cell growth and overall metabolic homeostasis. Hexokinase is the enzyme responsible for converting glucose into glucose-6-phosphate, which is subsequently used by glycolysis, the pentose phosphate pathway, and the hexosamine biosynthetic pathway. As such, perturbation of endogenous hexokinase function could significantly hinder neuronal metabolism by affecting glucose utilization by these key metabolic pathways. Here, we demonstrate that the glucose analogue 2-deoxyglucose (2DG) decreases cell viability, as well as both basal and maximal mitochondrial oxygen consumption in response to the neurotoxic lipid 4-hydroxynonenal (HNE), whereas glucose deprivation has a minimal effect. Furthermore, using a cell permeabilization assay we found that 2DG has a more pronounced effect on HNE inhibition of mitochondrial complex I and II than glucose deprivation. Importantly, these findings indicate that altered glucose utilization plays a critical role in dictating neuronal function and survival by regulating the mitochondrial response to electrophilic stress.